Legal Protection Of Waqf (Wakaf) Land Through Act - Law No. 5 Of 1960 Concerning The Fundamental Regulations Of Agraries (Case Study Of Land In Semarang City) - Dodi Irama; Zudan Arief Fakrulloh; Azis Budianto (Journal Research of Social Science, Economics, and Management, 2023)
The land legal certainty is necessary to have a rule of law. This is because in every settlement of cases of conflicts and land disputes, certainty regarding the land is needed, including knowing the status of the land, who owns it, what the evidence is, and knowing its location and extent, to guarantee legal certainty regarding the matters mentioned above to avoid the existence of an acknowledgment and expropriation and a party that recognizes the unilateral land. Empowerment of Waqf in Indonesia, judging from the amount, the waqf property itself can be said to be quite large. Most of the items that will be waqf are plots of land that will be built by places of worship, Islamic educational institutions, cemeteries, or other things which are generally not cheap. Waqf objects have useful value, namely, they are managed by very good or modern management, but must be based on the Islamic Religion Shari'ah under the coordination of the Indonesian Waqf Board. This research method is research that uses a normative juridical research approach. This approach examines legal issues based on normative rules associated with existing conditions in society.